Microfluidics in Microstructure Optical Fibers: Heat Flux and Pressure-driven and Other Flows - Florides, Georgios A.; Kalli, Kyriacos; Lazari, Lazaros; Komodromos, Michael; Dias, Frederic; Christodoulides, Paul; Koutsides, Charalambos (My University, 2013)
Microfluidics are important micro-scale devices that can be used to manipulate very small volumes of fluids on the order of nano- to femto-liters. The control and sorting of nano-particles is a primary goal using this technology. There is particular interest in the use of microstructure optical fibers for the heat transfer of fluids, whereby the guided light interacts with a fluid in the region of the air-hole structure. We study the fluid transport capabilities of microstructure fibers with cross sections containing circular or elliptical holes, considering the effects of flow rates, fluid viscosity, and the channel shape. The role of heat flux is considered in relation to the fluid characteristics. Results can be obtained through the solution of the time-dependent Navier-Stokes equations and the convection-diffusion equation. This work is of importance as one cannot assume that the flow dynamics in microstructure fibers will be the same as conventional micro-fluidic channels. Through the study of the heat transfer, for pressure-driven and other flows and for low Reynolds numbers, we confirm anticipated behavior of the fluids in the micro-channel structure.
Keywords: Microfluidics; Microstructure optical fiber; Fluid flow; Heat flux